LEGAL PROTECTION FOR HEALTH WORKERS IN HANDLING EMERGENCY PATIENTS - Widodo, Nanang; Adam HR, Muhammad (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The objective of this article's research is to ascertain the legal protection of healthcare professionals who provide emergency patient care. A qualitative research method with a descriptive approach that is juridically normative is employed. Literature analysis is implemented as the methodology for data acquisition. The findings indicated that health professionals are legally and ethically obligated to provide assistance to all emergency patients, even if the action is taken without the patient or family's consent, as the objective is to prevent patients from suffering disability and saving lives. Legal protection must be provided to health personnel who engage in such behaviours. The author's recommendation is that all health facilities establish standard operating procedures for the treatment of emergency patients. These procedures serve as a legal foundation for health personnel to provide assistance to emergency patients.